Respon Pertumbuhan dan Produksi Tanaman Sawi (brassica juncea l.) terhadap berbagai Dosis Pupuk Organik Cair - Astuti. M; Trisnawaty AR; Muhanniah Muhanniah (Journal of Innovative and Creativity, 2025)
The use of livestock manure processed into liquid organic fertilizer can enhance soil fertility in agricultural land. However, the utilization of this organic fertilizer is still uncommon among farmers, particularly in Sidrap Regency. This study aimed to assess the effect of different doses of liquid cow urine organic fertilizer on the growth and yield of mustard plants. The experiment was conducted at the experimental field of the Agrotechnology Study Program, Faculty of Science and Technology, Universitas Muhammadiyah Sidenreng Rappang, from December 2024 to February 2025. The study applied a Randomized Block Design (RBD) consisting of five treatments: liquid cow urine organic fertilizer at doses of 50 ml/polybag (P1), 100 ml/polybag (P2), 150 ml/polybag (P3), 200 ml/polybag (P4), and a control without fertilizer (P0), with three replications for each treatment, resulting in a total of 45 experimental units. Data were analyzed using ANOVA, followed by the Least Significant Difference (LSD) test at 1% significance. The results indicated that the application of liquid cow urine organic fertilizer at various doses influenced mustard plant growth, particularly in terms of leaf number, while other parameters showed no significant effect. The 50 ml/polybag dose produced the best results for plant height (22.3 cm) and leaf length (23.5 cm), the 100 ml/polybag dose yielded the highest fresh weight (24.10 g), and the 200 ml/polybag dose resulted in the highest number of leaves.